2018
DOI: 10.21608/zumj.2018.13266
|View full text |Cite
|
Sign up to set email alerts
|

The RELATION OF SERUM IRISIN LEVEL WITH METABOLIC AND HORMONAL CHANGES IN RAT MODEL OF POLYCYSTIC OVARY

Abstract: Background: Polycystic ovary syndrome (PCOS) is one of the leading causes of infertility in female. It is usually associated with insulin resistance (IR), obesity, hyperlipidemia, and type II diabetes. Irisin is amyokine which increases energy expenditure and protects against insulin resistance and obesity. There were controversial studies about the levels of irisin and its relation to hormonal and metabolic changes in PCOS. This study was designed to estimate serum level of irisin in letrozole-induced PCOS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The most accepted theory to explain the pathophysiology of the metabolic syndrome is insulin resistance ( Foda et al,2018). There was lower level of insulin in obese PCOS ladies compared with corresponding control, in contrary to the most other researches ( Foda et al ,2018) (Ibrahim et al ,2018.…”
Section: Discussionmentioning
confidence: 76%
“…The most accepted theory to explain the pathophysiology of the metabolic syndrome is insulin resistance ( Foda et al,2018). There was lower level of insulin in obese PCOS ladies compared with corresponding control, in contrary to the most other researches ( Foda et al ,2018) (Ibrahim et al ,2018.…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, it is known that testosterone levels are associated with muscle mass increase and protection from muscle atrophy (10,11). The literature regarding the relationship between serum irisin and testosterone levels is inconclusive, with studies reporting both negative and positive associations between the two hormones (12,13). In addition, it has been shown that BFR exercise can achieve higher testosterone levels compared to high-intensity resistance exercise, but not significantly higher (14).…”
Section: Introduction Introductionmentioning
confidence: 99%